«Which of You Is Ready to Take a Leap to the Emptiness Today»? - Yu. A. Lukin (Высшее образование в России)
In any academic discipline of higher professional education, the introductory (first) lecture is extremely important. In the didactic aspect, the  development of students’ motivational sphere during this first class has a  priority meaning. Drawing on our own pedagogical experience, we offer two  variants of the decision of this priority task, which determine the content of the introductory lecture. In the first case, a teacher and students discuss a well-known parable of the three builders of a temple and the ideas of E.  Fromm’s book “To Have or to Be?” The second variant was applied at the  introductory lecture on didactics for second-year students of the Physics and  Mathematics Faculty of the Voronezh State Pedagogical University this  February. We compared two historical facts: planning of the expedition by C.  Columbus and M. Lomonosov’s departure from his home. The Nobel laureate  in physics W. Heisenberg interpreted the first event as a “leap to the  emptiness.” The objective comparison of the above-mentioned facts indicated who had actually done this Act – the leap to the emptiness. The  quintessence of the introductory lecture was a question proposed to students  and put to the title of this article. The further discussion of M.V.  Lomonosov’s life and work became the statement of the system-forming role  of the motivational component in the structure of any kind of human activity  (including educational). The second variant of holding the first lecture has  shown the greater incentive on students’ motivation. The examination of the  scientific foundations of the principles of scientific organization of labor,  effective methods of scientific organization of intellectual work, psychological  foundations of educational and cognitive activity became the logical  continuation of the discussion of the motives of educational and cognitive  activity.